2006
DOI: 10.1007/s11243-005-6372-5
|View full text |Cite
|
Sign up to set email alerts
|

A Stopped-flow Study on the Kinetics and Mechanism of CO2 Uptake by the cis-[Cr(1,10-phenanthroline)2(OH2)2]3+ Complex Ion

Abstract: The kinetics of the reaction between gaseous CO 2 and the cis-[Cr(phen) 2 (OH 2 ) 2 ] 3+ ion leading to the formation of the carbonato complex ion, have been studied over the pH and temperature ranges: 3 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The substrate and product of the second step were identified by rapid-scan spectra. The maximum value of absorbance (k 495:91 nm) for the final product of acid hydrolysis of the cis-½Cr(phen) 2 ðO 2 COÞ þ ion is the same as for cis-½Cr(phen) 2 ðOH 2 Þ 2 3þ (Figure 3), which was a substrate in the CO 2 uptake reaction [5]. Based on the results obtained, the mechanism of acidcatalyzed hydrolysis of cis-½Cr(phen) 2 ðO 2 COÞ þ was suggested, which is presented in the Scheme 1.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The substrate and product of the second step were identified by rapid-scan spectra. The maximum value of absorbance (k 495:91 nm) for the final product of acid hydrolysis of the cis-½Cr(phen) 2 ðO 2 COÞ þ ion is the same as for cis-½Cr(phen) 2 ðOH 2 Þ 2 3þ (Figure 3), which was a substrate in the CO 2 uptake reaction [5]. Based on the results obtained, the mechanism of acidcatalyzed hydrolysis of cis-½Cr(phen) 2 ðO 2 COÞ þ was suggested, which is presented in the Scheme 1.…”
Section: Resultsmentioning
confidence: 90%
“…Since the determined values of stability constants of complex ion studied were as follows: pK 1 =2.9 and pK 2 =5.9 [5], we studied the reaction of CO 2 with cis½Cr(1,10-phenanthroline) 2 ðOH 2 Þ 2 3þ ion in acidic solution.…”
Section: Introductionmentioning
confidence: 99%
“…The pK values for the acid dissociation of cis -[Cr(C 2 O 4 )(BaraNH 2 )(OH 2 ) 2 ] + were determined spectrophotometrically over 340/700 nm range. Then, the pK 1 and pK 2 values in the ground state were computed using Origin 8.5 program, based on absorbance variations at a selected wavelength and applying the non-linear least squares method according to the Equation (7) [30]: where [H 2 A], [HA - ] and [A 2 - ] denote cis -[Cr(C 2 O 4 )(BaraNH 2 )(OH 2 ) 2 ] + , cis -[Cr(C 2 O 4 )(BaraNH 2 ) (OH 2 )(OH)] and cis -[Cr(C 2 O 4 )(BaraNH 2 )(OH) 2 ] - , respectively, at a particular wavelength l. Absorption spectra in the UV-visible region were measured using a Perkin-Elmer Lambda 650 spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…Interesting seems to be comparison of reactions of carbon dioxide uptake by complexes of Chromium(III) with organic ligands; such as methyl 3-amino-2,3-dideoxy-α-Darabino-hexopyranoside (AaraNH 2 ) [2], histamine (hm), pyridoxamine (pm) [3] and 1,10-phenanthroline (phen) [4]; and by complexes of Co III with NH 3 as ligand. Spectroscopic and kinetic studies of CO 2 addition reaction to inert co-ordination compounds of Cr III showed that mechanism of these reactions occurs also through two steps: addition of the adduct molecule (carbon dioxide), which runs fast and creation of the carbonate chelate ion (ring closure).…”
Section: The Second Step ؊ Closure Ring By Carbonate Ionmentioning
confidence: 99%
“…(2) (3) and only 2Ϫ3 % dissolved CO 2 constitute H 2 CO 3 . The hydration equilibrium of CO 2 is given by: (4) for which the equilibrium constant, K hyd ϭ K 2 /K 1 , based on K 1 ϭ 1.72 ϫ 10 Ϫ4 and K 2 ϭ 4.48 ϫ 10 Ϫ7 [8]. This values indicate that the hydrolysis equilibrium of CO 2 is far moved to the left.…”
Section: Introductionmentioning
confidence: 99%